In vitro activity of tigecycline against patient isolates collected during phase 3 clinical trials for hospital acquired pneumonia - Peter J. Petersen; Margareta Tuckman; Hal Jones (MDPI AG, 2010)
The in vitro activity of tigecycline was evaluated against 819 baseline pathogens isolated from 383 patients enrolled in the phase 3 clinical trial investigating the efficacy of tigecycline in hospital acquired pneumonia (HAP). The trials were global, enrolling patients in 27 countries. Tigecycline was active against the most prevalent pathogens in HAP, including gram-positive and gram-negative strains (90% of MICs ≤2 μg/mL for the entire collection). The spectrum of activity of tigecycline included important pathogens such as Staphylo- coccus aureus (including methicillin-resistant S. aureus), Enterococcus faecalis, Streptococcus pneumoniae, Acinetobacter baumannii/calcoaceticus complex, Escherichia coli, Klebsiella pneumonia, and Enterobacter cloacae. As reported previously, a few genera, such as Pseudomonas aeruginosa and the Proteeae, were generally less susceptible to tigecycline by comparison to other gram-negative pathogens. The excellent in vitro, expanded, broad-spectrum activity of tigecycline in the clinical isolates confirmed the potential utility of tigecycline for pathogens associated with with hospital acquired pneumonia infections.